Muslimah’s Clothing Brand, Identity, and Myths in Barthes Semiotic Study - Wardiani, Sri Rijati (UIN Maulana Malik Ibrahim Malang, 2019)
This study discusses the phenomenon of the proliferation of Muslimah clothing products along with the wave of ‘Hijrah’ movement in Indonesia. Muslimah clothing is displayed with a variety of brands which are related to certain classes and identities. Muslimah clothing also contains myths in the context of Barthes. The purpose of this study is to reveal the relationships between these variables. The study employed a qualitative description method with Barthes’s semiotic theory through the stages of denotation and connotation analysis. The results of the study indicate the relationship between brand and consumer identity. Muslimah clothing is a marker (acoustic image), and as the symbols (concepts) are “clothing and accessories used by Muslim women.” The relationship (sign) between markers and symbols, in this case, is a religious relationship. Penelitian ini mendiskusikan fenomena maraknya produk busana muslimah seiring dengan gelombang gerakan ‘hijrah’ di Indonesia. Busana muslimah ditampilkan dengan beragam brand yang bila dikaji terkait dengan kelas dan identitas tertentu. Di dalam busana muslimah juga terkandung mitos dalam konteks Barthes. Tujuan penelitian ini adalah mengungkap relasi di antara variabel-variabel tersebut. Kajian menggunakan metode deskripsi-kualitatif dengan teori semiotika Barthes melalui tahapan analisis denotasi dan konotasi. Hasil penelitian menunjukkan keterkaitan antara brand dan identitas konsumen. Busana muslimah adalah penanda (gambaran akustik),sedangkan yang menjadi petanda (konsep) adalah ‘busana dan kelengkapannya yang digunakan oleh perempuan beragama Islam’. Hubungan (tanda) di antara penanda dan petanda dalam hal ini adalah relasi keagamaan.